Система гидродинамических уравнений, описывающих ламинарное течение в соосных конических каналах постоянной ширины - Ульев, Леонид Михайлович (НТУ "ХПИ", 2005)
In this paper, the set of hydrodynamic equations is obtained for description of steady state laminar axisymmetric flow of Newtonian liquid in coaxial conic channels with constant width. Complete set of hydrodynamic equations is presented in resultant stresses. The estimation of equations numbers is executed for important industrial cases and simplified equations are noted in Oseen form both for diffuser and confusor flow.
Keywords: вязкая жидкость; конфузорное течение; дроссельное регулирование; конструирование проточных частей